Asynchronous fault location scheme for half‐wavelength transmission lines based on propagation characteristics of voltage travelling waves. Issue 4 (31st January 2019) - Nan, Peng; Menghan, Cheng; Rui, Liang; Zare, Firuz
Abstract : Due to prominent attenuation of travelling waves, double‐end fault location method produces considerable errors when applied to ultra‐high voltage AC half‐wavelength transmission (UAHT) lines. In order to address this problem, this study presents a novel fault location scheme based on the attenuation, refraction and reflection principles of aerial‐mode voltage travelling waves (AVTWs). In the scheme, the faulted section of an UAHT line is first determined according to the accumulated amplitude ratio of the pre‐determined frequency components of AVTWs asynchronously sampled at both terminals of the line. Then, the Teager energy of the first two wavefronts of the AVTW – measured at the terminal in the faulted section – is used to define two factors for selecting the appropriate accurate fault location method. Finally, the single‐end travelling wave method is adopted for locating the faults near the line terminal. The presented double‐end method utilises the amplitude ratio of AVTWs to locate the faults far from the line terminal. A 1000 kV UAHT line model is considered with various fault conditions in PSCAD/EMTDC simulations. The simulation results and analysis demonstrate that the proposed fault location scheme is accurate and immune to fault distances, fault types, fault impedances and fault inception angles.